Public Records and Management of Information Materials in Nigerian Local Government: A Transformative Route (Global Journal of Human-Social Science, 2018)
In every organization, set objectives had always remained paramount for its growth and delivery of quality services. Local government like every other organization has its objectives to be achieved and these could only be delivered through effective and efficient utilization and management of information and records at its disposal. Worrisome is the continued existence of the institution of local government in Nigeria which has in the recent time attracted many criticisms due largely to serial poor performances in achieving quality service delivery to the people within its area of jurisdiction. However, it is against this established premise that the paper sets to appreciate available information materials and records management for quality service delivery in Nigerian local government system. Methodologically, the study adopts qualitative method and data were ostensibly generated through secondary sources of data collection and analyzed in content.
Keywords: local government; nigeria; records; registry; service delivery